Atmospheric drivers of winter above‐freezing temperatures and associated rainfall in western Canada. (24th June 2019) - Newton, Brandi W.; Bonsal, Barrie R.; Edwards, Thomas W. D.; Prowse, Terry D.; McGregor, Glenn R.
Abstract: Winter thaw episodes, especially when accompanied by rain, can significantly deplete the winter snowpack, which is a critical water storage component in the mountainous headwater regions of the major river basins of western Canada. Here we identify the characteristic synoptic‐scale mid‐tropospheric atmospheric circulation regimes that tend to foster such extreme hydrologic events using self‐organizing map analysis of meteorological reanalysis data from 1949 to 2012. Daily winter 500 hPa geopotential height fields over the Pacific Ocean and western Canada are classified into 12 dominant synoptic types, for which conditional probabilities of above‐freezing temperatures and rainfall are then calculated and mapped using daily high‐resolution gridded data. Results show that above‐freezing surface air temperatures and rain events in winter are commonly associated with the occurrence of a ridge of high pressure over western Canada, which induces southwesterly advection of relatively warm, moist maritime air masses into the continental interior, and that the intensity and spatial footprint of the surface climate response is related to the strength and position of the ridge. Conversely, the development of a ridge of high pressure over the Pacific Ocean and adjacent trough of low pressure over western Canada, which favours northwesterly to westerly mid‐tropospheric flow over the continental interior in winter, tends to suppress the occurrence of above‐freezing temperatures and rain. The synoptic type most strongly associated with winter thaw and rain events underwent a statistically significant step‐change increase in mean frequency in 1977, accompanied by a corresponding step‐change decrease in the frequency of the dominant synoptic type depicting westerly (zonal) circulation, coinciding with a well‐documented shift to a positive phase of the Pacific Decadal Oscillation. Abstract : Classification of daily winter (DJFM) 500 hPa geopotential heights from 1949 to 2012, using self‐organizing maps, reveals dominant mid‐tropospheric circulation patterns affecting hydroclimatic variables conducive to snowmelt in western Canada. A ridge of high pressure over western Canada is associated with a greater probability of above‐freezing temperatures and rainfall, compared with zonal flow or a trough of low pressure over the same region.